234k views
3 votes
Simplify
-4r + S - 2r - 3s

2 Answers

4 votes

Answer:-6s-2r

Explanation:

you must add all like terms in this case S -4-3 is -7. -7+1=-6.
-6s-2r

User Maksim Eliseev
by
5.1k points
0 votes

Answer:

-6r - 2s

Explanation:

Given expression,

→ -4r + s - 2r - 3s

Let's simplify the expression,

→ -4r + s - 2r - 3s

→ (-4r - 2r) + (s - 3s)

→ -6r + (-2s)

→ -6r - 2s

Hence, the answer is -6r - 2s.

User Excellent
by
5.2k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.